2016
DOI: 10.1111/1753-0407.12475
|View full text |Cite
|
Sign up to set email alerts
|

Glycation and cardiovascular disease in diabetes: A perspective on the concept of metabolic memory

Abstract: Epidemiological studies have suggested that cumulative diabetic exposure, namely prolonged exposure to chronic hyperglycemia, contributes to the increased risk of cardiovascular disease (CVD) in diabetes. The formation and accumulation of advanced glycation end-products (AGEs) have been known to progress under hyperglycemic conditions. Because AGEs-modified collagens are hardly degraded and remain in diabetic vessels, kidneys and the heart for a long time, even after glycemic control has been achieved, AGEs co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
66
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 85 publications
(210 reference statements)
0
66
0
5
Order By: Relevance
“…In diabetic myocardium, mitochondria is deemed as one of the major sources of free radicals. Numerous studies have reported that hyperglycemia markedly impaired mitochondrial morphology and function, causing electron leakage and O 2 •− generation2526. The enhanced oxidative stress has been confirmed to be a key contributor to increased myocardial vulnerablility to MI/R injury25.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In diabetic myocardium, mitochondria is deemed as one of the major sources of free radicals. Numerous studies have reported that hyperglycemia markedly impaired mitochondrial morphology and function, causing electron leakage and O 2 •− generation2526. The enhanced oxidative stress has been confirmed to be a key contributor to increased myocardial vulnerablility to MI/R injury25.…”
Section: Discussionmentioning
confidence: 99%
“…To make things worse, the long-term prognosis is also much worse than non-diabetic individuals with higher rates of residual ventricular dysfunction and overall mortality2324. So far, the mechanisms have not been fully elucidated, but prolonged hyperglycemia-enhanced oxidative stress was indicated to be a crucial contributor25. Owing to its critical role in generating ATP and ROS, cardiomyocyte mitochondria has been specifically investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is one mechanism that participates in the establishment of microvascular [69] and macrovascular [70] complications even after maintenance of normoglycemia under intensive antihyperglycemic treatment, a phenomenon often referred to as “metabolic memory.” In front of this, complementary therapies targeting not only the hyperglycemia but also other metabolic disturbances in diabetes mellitus (DM), such as oxidative stress, are appearing as promising strategies in combating diabetic complications [71]. …”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16] There is accumulating evidence to show the pathophysiological involvement of "metabolic memory" in vascular complications in diabetes. 17 Indeed, although intensive management of blood glucose for 6.5-10 years did not significantly reduce the risk of CVD or death in both type 1 and 2 diabetic patients, the 10-30-year follow-up studies sured as skin autofluorescence (SAF) by an AGE-Reader (Diagnoptics, Groningen, Netherlands). 24,25 SAF is defined as the ratio of average autofluorescence over the entire 420-600-nm emission spectrum to that over 300-420 nm, which correlates with pentosidine and N ε -(carboxymethyl) lysine (CML), well-characterized fluorescent and nonfluorescent AGEs, respectively, in the skin.…”
mentioning
confidence: 99%